Survey on the Use of Learning Management System (LSM) for Learning at As-Shalihin Islamic Boarding School - Usman, Asep Tutun; Alimudin, Alimudin; Permadi, Asep Angga (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
Along with the development of globalization, especially related to the acceleration of science and technology, Islamic boarding schools are faced with socio-cultural changes that require Islamic boarding schools as non-formal educational institutions to modernize the education system, the presence of the Learning Management System (LMS) media as a learning tool can help modernize success, because LMS can become learning tools, learning resources, and learning support facilities that will be easily absorbed by students with appropriate and effective methods and foster independence because they can be accessed alone using a PC even though it is used in a teacher's guide or monitoring. The method used in this study is a quantitative method with a descriptive approach and survey techniques. The population in this study were the As-Salihin Malangbong Garut Islamic boarding school students, totaling 75 students. The survey results show an average of 75.23%. This is corroborated by the results of the direct observation of the researchers that the students at the As-Shalihin Islamic Boarding School are familiar with various kinds of Learning Platforms such as: Classroom, Noodle, Qubisa. as many as 11% of students always use the LMS platform as learning, 21% often, sometimes 56%, rarely 8% and never use the LMS platform as a learning medium as much as 4%. It is hoped that this survey will be used as a follow-up in encouraging learning by modernizing with the LMS platform so that it becomes a pilot plan for the development of learning in Islamic boarding schools where in Garut district there are 1030 Islamic boarding schools but only 41 Islamic boarding schools already have website data